DYNAMICS OF GENDER ROLES IN RICE FARM LAND MANAGEMENT IN BENGKULU CITY - Vanesa Putri Cahyani; Satria Putra Utama; Bembi Akbar Serawai; Moh. Saeri (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
This study aims to analyze the dynamics of gender roles in rice farming management and the challenges of gender roles in rice farming. It uses a mixed methods approach with descriptive quantitative and qualitative analysis. Data analysis is conducted using the Gender Analysis Matrix (GAM), which includes aspects of labor, domestic activities, resources, and socio-cultural factors.The results show that men are still dominant in labor indicators (61.94%), resource indicators (54.52%), and socio-cultural indicators (55.24%), while women have a significant contribution in domestic activities (57.29%). In terms of access and control, women’s roles are still relatively lower than men’s. The study indicates that although women contribute to rice farming, their roles are not balanced with access and control, especially in asset ownership, access to assistance, and involvement in decision-making. The novelty of this research lies in the use of the Gender Analysis Matrix (GAM) approach to examine gender role dynamics in rice farming management. Overall, gender dynamics in rice farming still show inequality, where men are more dominant in production activities and decision-making, while women tend to have a higher workload. The main challenges are related to the limited access and control of women in managing rice farming.